Risk of sleep disorders in patients with pneumoconiosis: a retrospective cohort study - Yen-Sung Lin; Te-Chun Shen; Cheng-Li Lin; Chih-Yen Tu; Te-Chun Hsia; Wu-Huei Hsu; Der-Yang Cho (Springer, 2024)
Abstract Background Pneumoconiosis is associated with pulmonary and cardiovascular diseases; however, the link between pneumoconiosis and sleep disorders is not well understood. This study aimed to investigate the connection between pneumoconiosis and subsequent risk of sleep disorders. Methods This population-based retrospective cohort study used data from the National Health Insurance database in Taiwan. The pneumoconiosis cohort consisted of 13,329 patients newly diagnosed between 2000 and 2015. The comparison group included 53,316 age-, sex-, and diagnosis date-matched individuals without pneumoconiosis. The development of sleep disorders was monitored until the end of 2018. Cox proportional hazard regression models were used for risk assessment. Results The incidence of sleep disorders was 1.31 times higher in the pneumoconiosis cohort than in the comparison cohort (22.8 vs. 16.2 per 1000 person-years). After controlling for age, sex, comorbidity, and medication, the adjusted hazard ratio (aHR) was 1.24 (95% confidence interval [CI] = 1.17-1.32). Stratified analyses by age group, sex, and comorbidity status showed significant associations between pneumoconiosis and sleep disorders (aHRs, 1.19-1.64). In addition, patients with pneumoconiosis had a significantly increased risk of developing sleep apnea (aHR = 1.71, 95% CI = 1.31-2.22). Conclusion This study demonstrates that patients with pneumoconiosis are at a higher risk of developing sleep disorders and sleep apnea. Healthcare professionals should pay close attention to sleep quality and disturbances in patients with pneumoconiosis.